Radio frequency identification technology adoption: South African retailers' perspecitve - Sarpong, Bernard Oppong (My University, 2013)
In recent years, Radio Frequency Identification (RFID) Technology has transformed from being unknown to mainstream applications that help facilitate the managing of manufactured goods and materials. Its information storage capacity as well as its ability to transfer information through contactless means without line-of-sight translates to significant advantages to deliver various benefits for retailers and their clients in the retail settings. However, up until now RFID technology has gained very little momentum and the status of adoption particularly of retail organisations in South Africa is unknown. To fill this research gap, an exploratory study that draws on the Technology-Organisation-Environment (TOE) framework was employed to provide a deeper understanding of South African retailers’ perceptions of RFID adoption. Five interviewees representing their respective organisations participated in the study. The findings suggested that the adoption level is very low and only one organisation from the sample used had done a pilot project. The results also indicated that cost, standardisation and government support influenced the adoption of the technology. Complexity and technology competence were not considered to have any influence in the adoption of the technology. Competitive pressure was not deemed influential if the technology was not embedded in the whole supply chain, a somewhat surprising result. There were no anticipated impacts on the employees if this technology was implemented. Methodological and practical implications are also discussed.
Research report submitted to the School of Economic and Business Sciences, Faculty of Commerce, Law and Management, University of the Witwatersrand, 2013.
Keywords: RFID; Radio frequency identification technology; South Africa; Retail organizations; Adoption